'I want to join the play'. Young children's wants and needs of empathy when experiencing peer rejections in ECEC. Issue 4 (20th October 2022) - Nergaard, Kari
ABSTRACT: Peer rejections impair children's well-being in ECEC, impede their social and emotional development, and increase the risk of multiple forms of peer adversities. This study explores children's need for empathy when experiencing rejections from peers in free play situations in ECEC. The data were collected through video-recorded dialogical interviews with children between three and a half and six years of age and analysed within a phenomenological hermeneutical approach. The findings show that children's need for empathy was most dominantly initiated by the wish to play and experience belonging, and this need was felt in relation to other children as well as ECEC staff. The findings highlight the importance of the ECEC practitioner's being present and available for emotional and social support for children in play negotiations, as well as her or his involvement in facilitating participation, encouraging children's empathic expressions, and promoting inclusion.